Organic geochemical, palynofacies, and petrographic analyses examining the hydrocarbon potential of the Kharita Formation (Albian) in the Matruh Basin, northwestern Egypt. (February 2020) - Deaf, Amr S.; Tahoun, Sameh S.; Gentzis, Thomas; Carvajal-Ortiz, Humberto; Harding, Ian C.; Marshall, John E.A.; Ocubalidet, Seare
Abstract: A recent study of selected samples from the Cretaceous (Albian) Kharita Formation of Egypt revealed very good to excellent source rock (SR) potential for six intraformational, organic-rich intervals. This work investigates the SR potential of the entire Kharita Formation across the Matruh Basin, using samples from two wells: the Abu Tunis 1X well from the central part of the basin, and the Siqeifa 1X well drilled on the eastern margin of the basin. More strongly reducing conditions were developed in the centre of the basin, and resulted in the deposition of more organic-rich shales by comparison to the less reducing conditions that prevailed on the eastern basin margin, where the shales contain less organic matter. Deltaic intraformational shales and carbonates in the Kharita Formation of Abu Tunis 1X constitute a significant 120 m net of the potential SR. The lower Kharita Formation contains 34 m net shale SR of good to very good/excellent organic richness, yielding values of 1.14–11.59 wt % total organic carbon (TOC). The organic matter has low Hydrogen Index (HI) values (184–389 mg HC/g TOC) and amorphous organic matter (AOM) and relatively high non-opaque phytoclast frequencies indicating mainly gas/oil-prone organofacies (kerogen Types III/II). The upper Kharita is rather important, containing 86 m net shale/carbonate SR that has fair to good organic richness (0.8–1.8 wt % TOC), and lower HI (126–250 mg HC/g TOC), a dominance of non-opaque phytoclasts, and subordinate AOM frequencies, which together indicate gas/oil-prone organofacies (kerogen III/II). In the Siqeifa 1X well, Kharita deltaic intraformational shales and shaley dolostones comprise 80 m net SR, which has mainly fair to good to less very good organic richness (0.8–2.1 wt % TOC), whilst low HI (93–220 mg HC/g TOC), dominance of non-opaque phytoclasts and subordinate AOM indicate gas-prone organofacies (kerogen Type III). A relative upward increase in deposition of lignite and coaly carbonaceous material supports a gas-prone organofacies. Whilst thermal maturity indices only point to immature to early mature (pre- to early oil-window) SRs in both the Abu Tunis 1X and Siqeifa 1X wells, hydrocarbon exploration focussing on this potential source rock may be justified in areas to the southeast of the Matruh Basin, where modelling indicates this unit may have reached the late mature oil- to main gas-generation windows. Highlights: Intrabasinal variation in lithofacies, organic facies/richness, and organic quality are documented for the Cretaceous Kharita Formation of the Matruh Basin, Egypt. Reducing conditions at the depocentre led to deposition of organic-rich gas/oil-prone deltaic shales in the lower Kharita Formation. Oxic conditions at the basin margin led to deposition of organic-lean gas-prone deltaic shales in Kharita Formation. Reflectance and Rock-Eval data indicate immature to marginally mature source rocks in both the basin centre and marginal areas. As the southeastern part of the Matruh Basin is known to have reached thermal maturity, the Kharita Formation should be a suitable exploration target.